2017
DOI: 10.21859/cej-030913
|View full text |Cite
|
Sign up to set email alerts
|

Water Management Using System Dynamics Modeling in Semi-arid Regions

Abstract: Quantitative control and safe exploitation of water resources are crucial components for the sustainable development of any region due to increasing water scarcity, especially in arid and semiarid regions. A proper water resources management program of the Tabriz plain is necessary because of the groundwater excessive exploitation and the surface water limitations. The present study aims to develop a system dynamics (SD) model not only to identify safe groundwater level fluctuations and exploitation but also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…The stock-and-flow diagram is an algebraic representation of the model based on the causal loops that have been identified. Stock characterizes the state of the system and retains a memory of it, which enables description of its status; flow causes the stock to change via inflow or outflow for a period of time and interlinks the stock within the system; the auxiliary variables are the rates to determine the flow values for the period of time [38]. The general graphical expression of the stock-and-flow diagram is shown in Figure 4.…”
Section: Conceptual Framework Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The stock-and-flow diagram is an algebraic representation of the model based on the causal loops that have been identified. Stock characterizes the state of the system and retains a memory of it, which enables description of its status; flow causes the stock to change via inflow or outflow for a period of time and interlinks the stock within the system; the auxiliary variables are the rates to determine the flow values for the period of time [38]. The general graphical expression of the stock-and-flow diagram is shown in Figure 4.…”
Section: Conceptual Framework Analysismentioning
confidence: 99%
“…According to Ref. [38], the state equation between stock and flow can be mathematically described as follows:…”
Section: Conceptual Framework Analysismentioning
confidence: 99%
“…If an initial increase in a variable eventually results in a decreasing effect on the same variable, then the feedback loop is identified as a negative, counteracting or balancing' loop [22] [23].…”
Section: Causal Loop Diagrammentioning
confidence: 99%
“…The results showed that SD accurately calculated uncertainties in the major parameters. Nassery et al (2017) identified safe groundwater level fluctuations, the water supply and deficits of municipal-industrial and agricultural uses using SD in the Tabriz plain, Iran.…”
Section: Introductionmentioning
confidence: 99%